Knowledge Map of the Virtual Economy : Converting the Virtual Economy into Development Potential - Lehdonvirta, Vili; Ernkvist, Mirko (World Bank, Washington, DC, 2017)
The report is structured as follows. The next section introduces the theoretical notion of a 'virtual economy' and explains how it is distinct from other Information and Communication Technology (ICT)-related economic activities. The following sections describe in detail the main areas of the virtual economy, their economic impact, business models and value chains. The two major areas of the existing virtual economy are identified as: 1) third party gaming services and 2) microwork. This report will focus largely on these two distinct but conceptually related areas. Gaming services is an established industry that provides a rich set of evidence for analysis, while microwork is an emerging industry with apparently significant development potential. Other existing activities within the virtual economy are categorized as: 3) marketing related paid-for connections in social media ('cherry blossoming') and 4) user-created virtual goods in virtual environments. These are not covered in detail due to their limited development potential, at least at present. The sixth section analyzes the development potential of the virtual economy. Development potential is here understood as the ability to provide income to local economies through employment and entrepreneurial opportunities. Both short-run opportunities and long-run income development are considered. Development potential also includes the ability to support the development of local ICT infrastructure. In the final section, the report summarizes the key findings, identifies important gaps in current knowledge, and sketches out the scope for possible donor or Non-Governmental Organization (NGO)-led interventions towards maximizing the development potential of the virtual economy.